Study of clinical and biochemical profile of scrub typhus in a tertiary care hospital of West Bengal - Mandal, Rakesh; Guha Banerjee, Sarmila; Sinha, Arunima; Bandyopadhyay, Ujjwal; Sinha, Arijit (Asian Journal of Medical Sciences, 2023)
Background: Humans are accidental hosts in the zoonotic disease Scrub typhus. The disease though widespread in our county, it remains grossly underdiagnosed because of its non-septic clinical manifestations and lack of access to specific laboratory facilities. Aims and Objectives: The objective of present study is to evaluate the clinical presentations of Scrub Typhus among the study group. Furthermore, to assess the various laboratory findings in Scrub Typhus cases among the study group is the other objective of this study. Materials and Methods: The present study is an Institution-based, observational, and cross-sectional study conducted for 18 months with the admitted patients having 14–70 years of age. Data collected regarding patients’ demographic profile, symptoms, clinical findings, laboratory, and radiological findings. Data had been summarized as mean and standard deviation for numerical variables and count and percentages for categorical variables. Results: In our study, we found that most of the patients were 14–20 years old and female population was higher. It was found that 34.3% of patients had Eschar, 42.9% of patients had Rash, and 91.4% of patients had Pallor, 8.6% of patients had Ascites, 25.7% had Edema, 8.6% of patients had Jaundice, 11.4% had shock, and 57.1% had pneumonia/pneumonitis. The present study showed that 65.7% of patients had drug response (Doxycycline). Conclusion: Knowledge of geographical distribution, evidence of exposure to vector, clinical features such as fever, rash, eschar, headache, and myalgia along with high index of suspicion are crucial factors for early diagnosis and that helps in timely treatment of the cases.